Unique fingerprint of marine ectotherm body size change during hyperthermal crises - Paulina S. Nätscher; Kenneth De Baets; Wolfgang Kiessling (Proceedings of the National Academy of Sciences, 2026)
The term “Lilliput Effect” describes a substantial decrease in the average body size of fossil assemblages during major environmental perturbations in Earth’s history, which is reported in many paleontological studies. The limited regional, temporal and taxonomic focus of most studies, however, has sparked discussions concerning its generality. Additionally, even though a negative relationship between warming and body size has been established in recent marine ectotherms, the environmental and mechanistic drivers of the Lilliput effect are still debated. We compiled close to 9,000 body size changes from fossil, historical, and modern body size studies, to show that a decrease in body size is indeed a general response of marine ectotherms to environmental crises. The magnitude and temporal variability of size changes at the species-level are significantly higher during hyperthermal than nonhyperthermal events, suggesting differing mechanisms of body size decrease depending on the environmental stressor. Our results further show that ancient environmental perturbations with a higher magnitude of warming were associated with a greater dwarfing. This implies that warming was a major driver of body size decreases during hyperthermal events throughout the Phanerozoic, and future warming will impact current trajectories of body size reduction in modern marine ectotherms.